FINANCIAL MANAGEMENT AND ACCOUNTING EDUCATION IN IMPROVING THE VILLAGE LOCAL ECONOMY FOR MSMEs IN GODOBANGKONG VILAGE - Nugrahanti, Trinandari Prasetya; Lanjarsih, Laela; Mutumanikam, Primadonna Ratna (Universitas Pahlawan Tuanku Tambusai, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are crucial in driving local economic development in rural areas. However, these businesses often need help with financial management and accounting, limiting their growth and sustainability. This community service project aimed to enhance the financial literacy and accounting practices of MSME owners in a village setting to boost local economic development. The project employed a Participatory Action Research (PAR) method involving collaborative needs assessments, interactive workshops, practical exercises, and continuous feedback loops. The results demonstrated significant improvements in the participants' financial literacy, adoption of systematic bookkeeping practices, and access to micro-financing. Consequently, these advancements led to a 50% increased average monthly business income, enhanced cost management efficiency, and strengthened community support networks. In conclusion, the project successfully empowered rural MSME owners with essential financial management skills, contributing to sustainable local economic growth and providing a replicable model for similar initiatives in other rural communities.